2016
DOI: 10.1021/acscombsci.5b00193
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Doped NiFe2O4 Spinel as a Highly Efficient Catalyst for H2 Selective Catalytic Reduction of NO at Room Temperature

Abstract: H2 selective catalytic reduction (H2-SCR) has been proposed as a promising technology for controlling NOx emission because hydrogen is clean and does not emit greenhouse gases. We demonstrate that Pt doped into a nickel ferrite spinel structure can afford a high catalytic activity of H2-SCR. A superior NO conversion of 96% can be achieved by employing a novel NiFe1.95Pt0.05O4 spinel-type catalyst at 60 °C. This novel catalyst is different from traditional H2-SCR catalysts, which focus on the role of metallic P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…[26,27]) as well as the significant difference between the magnetocrystalline anisotropy, K V NFO = −6.2 × 10 3 J/m 3 and K V CFO = 2 × 10 5 J/m 3 , and the relatively high value of their magnetisation M S (M S CFO = 88 A•m 2 /kg and M S NFO = 55 A•m 2 /kg) [28,29]. While most works deal with iron oxides or Mn/Zn substituted ferrites as a soft phase, only a few works are devoted to nickel ferrite in core/shell systems [4,14,30], although nickel ferrite being a promising material for catalysis [31] and spintronics [32] applications.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27]) as well as the significant difference between the magnetocrystalline anisotropy, K V NFO = −6.2 × 10 3 J/m 3 and K V CFO = 2 × 10 5 J/m 3 , and the relatively high value of their magnetisation M S (M S CFO = 88 A•m 2 /kg and M S NFO = 55 A•m 2 /kg) [28,29]. While most works deal with iron oxides or Mn/Zn substituted ferrites as a soft phase, only a few works are devoted to nickel ferrite in core/shell systems [4,14,30], although nickel ferrite being a promising material for catalysis [31] and spintronics [32] applications.…”
Section: Introductionmentioning
confidence: 99%
“…Another important point is that the oxidation state of Pt is the controlling factor for NO-H 2 reaction activity, and the lower valence state of Pt may have the higher activity . As our previous studies on Pt doped Ni–Fe spinel oxides demonstrated, the Pt with different valence states favors NO adsorption on the Pt site . The investigation on Pt/carbon black also proves that some electrons transfering from Pt to the carbon, specifically at the interface of Pt–C, can enhance the activity by tuning the electronic structure of Pt.…”
Section: Introductionmentioning
confidence: 65%
“…14 As our previous studies on Pt doped Ni− Fe spinel oxides demonstrated, the Pt with different valence states favors NO adsorption on the Pt site. 17 on Pt/carbon black also proves that some electrons transfering from Pt to the carbon, 18 specifically at the interface of Pt−C, can enhance the activity by tuning the electronic structure of Pt.…”
Section: ■ Introductionmentioning
confidence: 80%
“…Moreover, the low H 2 concentration (< 1%) and operation temperature suggest H 2 -SCR is a safe J o u r n a l P r e -p r o o f 4 technology. Numerous supported/doped/encapsulated noble metal catalysts were already proposed and tested for H 2 -SCR [16][17][18][19][20][21][22][23], while different reaction mechanisms were presented.…”
Section: Introductionmentioning
confidence: 99%